A review of the family Alycidae (Acari, Acariformes) from North America - Uusitalo, Matti (Zootaxa, 2025)
A taxonomic study of the family Alycidae G. Canestrini & Fanzago in North America revealed four genera and nine species which are new to science: Alycus utahensis sp. nov. (Alycini), Amphialycus walteri sp. nov., Bimichaelia logani sp. nov., Glabromichaelia vazquezrojasi gen. and sp. nov., Laminamichaelia knowltoni sp. nov., Minimamichaelia gen. n., Odontoalycus exoculo gen. and sp. nov., Pachygnathus americanus sp. nov., Quartusmichaelia lanceolata gen. and sp. nov., Q. plumata gen. and sp. nov. (Bimichaeliini), and Petralycus obtusicornis sp. nov. (Petralycini). Redescriptions of 12 species, Alycus roseus C.L. Koch, 1842, A. denasutus (Grandjean, 1937), Amphialycus holarcticus Uusitalo, 2020, Orthacarus oblongus (Halbert, 1920) comb. and stat. nov., Bimichaelia pallida (Ewing, 1913), Minimamichaelia subnuda (Berlese, 1910) comb. nov., Quartusmichaelia setigera (Berlese, 1904) comb. nov., Q. shibai (Uusitalo et al., 2020) comb. nov., Q. dimixsetosa (McDaniel, 1980) comb. nov., Laminamichaelia arbusculosa (Grandjean, 1943), Petralycus celtisacinus McDaniel & Bolen, 1983, and P. caryapecaus McDaniel & Bolen, 1983, are based on the American material. Keys to the tribes, genera and species of Alycidae recorded so far in North America are provided.